Enhancing Rural Economic Potential through Ecosystem Profitability Analysis: A Strategic Approach for Ultra-Micro Enterprises. - Salat, Roy; Rinela, Yuniar Yesa; Chandramitasari, Widyaning; Wibawa, Tio Anta; Dewi, Nurma Gupita (Universitas YPPI Rembang, 2024)
Rural economies play a critical role in national development, yet their potential often remains underutilized due to structural and operational challenges faced by ultra-micro enterprises (UMEs). This study explores a strategic framework for enhancing rural economic potential through Ecosystem Profitability Analysis (EPA). EPA provides a holistic evaluation of interconnected economic activities within rural ecosystems, identifying synergies and gaps in resource allocation, market access, and value chain integration. By applying this approach, the study examines case studies of UMEs in rural regions, highlighting key success factors and barriers to scalability. Findings suggest that adopting EPA enables UMEs to optimize resource utilization, improve profitability, and strengthen their contribution to local economies. Recommendations are made for policymakers and development practitioners to incorporate EPA as a tool for fostering sustainable growth in rural enterprises. This research underscores the importance of ecosystem-based strategies in addressing systemic inefficiencies and empowering rural economic resilience.Keywords: Rural economics, ultra-micro enterprises, ecosystem profitability analysis, economic potential, strategic framework.